The specificity of autobiographical memory and imageability of the future. - Williams, J; Ellis, N; Tyers, C; Healy, H; Rose, G; MacLeod, A (1996)
Three studies examined whether the specificity with which people retrieve episodes from their past determines the specificity with which they imagine the future. In the first study, suicidal patients and nondepressed controls generated autobiographical events and possible future events in response to cues. Suicidal subjects' memory and future responses were more generic, and specificity level for the past and the future was significantly correlated for both groups. In the second and third studies, the effect of experimental manipulation of retrieval style was examined by instructing subjects to retrieve specific events or summaries of events from their past (Experiment 2) or by giving high- or low-imageable words to cue memories (Experiment 3). Results showed that induction of a generic retrieval style reduced the specificity of images of the future. It is suggested that the association between memory retrieval and future imaging arises because the intermediate descriptions used in searching autobiographical memory are also used to generate images of possible events in the future.